Comparative Analysis of Role of Vitamin E and Iron Supplementation for Weight Loss in Young Adult Obese Females with Controlled Diet of 1500 Calories - Sumetha Yaseen, Rubina Iqbal, Memoona Jahangir, Samia Arshad, Noor Ul Haq, Aiman Asif, Zari Salahuddin, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Obesity has become a major health issue in the world over past two decades. . This leads us to the need of immense exploration of life style modification options, dietary supplementation and weight loss friendly elements. Aim: Our study aims to highlight the comparative analysis of independent supplementation of vitamin E and iron to young adult females for their weight loss regime. Methods: 90 young adult non pregnant females of age between 25-39 years with BMI ranging between 30-34.9 (obese) were asked to take a fixed 1500 calorie diet for two months. They were divided into three groups with no supplement group, vitamin E group and iron group. Body mass index(BMI), LDL levels and prevalence of fatty liver was assessed among all individuals. Results: vitamin E and iron supplementation reduced BMI in their respective groups. Vitamin e and iron supplementation also reduce the prevalence of fatty liver among groups. Vitamin E reduces serum LDL levels. Conclusion: vitamin E and iron supplementation helps in weight loss. Keywords: obesity, vitamin E, iron, weight loss